Análise de minerais pesados de depósitos da formação itapecuru (cretáceo superior), bacia de São Luís: perfil cu-1, cu-2, cu-3, cu-4 e cu-5 - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1997)
Recent research focusing on faciologic and stratigraphic analysis of Cretaceous deposits in the São Luís Basin, state of MA, led to the recognition of two distinct estuarine units, formally designated the AIcântara Formation and the Cujupe Formation. Five subunits limited by erosive surfaces occur in the latter. The objective of this research was to determine the heavy mineral assemblage of the Cujupe Formation, comparing the results obtained for each of its five subunits. In a first phase of the work, samples were collected and analyzed for grain size distribution. Then, heavy minerals were separated and qualitative and quantitative analyses were performed. The samples analyzed are moderately to well sorted, very platicuritic to very leptocuritic, asymmetry from very positive to very negative, median of 2.90 and average clay content of 28%. Heavy mineral analysis led to the determination of an ultrastable assembly composed of opaques, zircon, tourmaline, staurolite and rutile. The staurolite is characteristically eroded at its edges by dissolution. No significant differences were observed in the mineralogical assembly in each subunit of the formation studied. The association of heavy minerals suggests source area predominantly composed of granites and metamorphic rocks. However, due to their sensitivity to weathering, transport, deposition, and diagenesis processes, heavy minerals do not necessarily accurately reflect the mineralogy of the source area.
Analysis of heavy minerals from deposits of the Itapecuru Formation (upper cretaceous), São Luís basin: cu-1, cu-2, cu-3, cu-4 and cu-5 profiles
Keywords: Minerais; Cretáceo; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA